Developing Tematic Economic Comic with Characters for Early Childhood - Rahmatullah Rahmatullah; Inanna Inanna; Muhammad Rakib; Mustari Mustari; Rabania Rabania (Universitas Negeri Makassar, 2020)
This study aims to develop a character economy comic for early childhood. This research is a type of research development (Research and Development) includes 5 stages, namely needs analysis; Identify the material to be developed; Development; Production; as well as the Trial stage. After the product has been designed, a material expert will assess the feasibility of the material content developed in a comic character design, as well as a design expert to assess the feasibility of the design side, both in the structure and appearance of the images as outlined in designing thematic economic comics. The data analysis technique used qualitative descriptive analysis and quantitative descriptive analysis. The results showed that thematic economic comics were feasible to be developed and tested on users based on the results of due diligence by experts. The average value of the results of the material expert trial was 4.7, while the results of the design expert's assessment obtained an average score of 4.5. The two results of the assessment are in the very feasible category for use in the field trial phase. After conducting field trials on elementary school level students, an average score of 4.7 was obtained and was in the very feasible category. Thus, it can be understood that the character economy comics that are developed can be a supplement in learning, especially in fostering children's economic character from an early age